Non-cardiac chest pain and psychological morbidity among patients cardiac emergency department and the emergency centre - Kristín Eva Rögnvaldsdóttir 1991- (2018)
Objective: The aim of this study was to assess the association of non-cardiac related visits and psychological morbidity among patients seeking help at the Cardiac Emergency Department and the Emergency Centre. Method: 390 patients aged 18-65 years old with presenting chest pain were contacted 1-8 month after discharge from the Cardiac Emergency Department and the Emergency Centre of the Landspitali National Hospital (LSH). Participants answered multiple standardized questionnaires which measure various psychological factors. Information about participants’ medical history was collected from medical files. Results: Non-cardiac chest pain was prevalent in the emergency departments at the Hospital in Iceland. Most participants (92%) who visited the CED or the Emergency Center of LSH with presenting chest pain, were diagnosed with non-cardiac chest pain and related diagnosis or had medical history of non-cardiac related visits. Participants with no history of cardiovascular disease were 75% and coronary heart disease patients were 25%. Depression and somatic symptoms were found to be significant predictors for non-cardiac related visits among CHD patients and somatic symptoms and health anxiety among NCCP patients Conclusion: The prevalence of non-cardiac related visits were associated with different psychological factors across groups, namely somatic symptoms and health anxiety among NCCP patients but somatic symptoms and depression among CHD patients. Keywords: Non-cardiac chest pain, coronary heart disease, NCCP patients, CHD patients, number of non-cardiac related visits, health-care contacts